Bird strike virtual testing simulations and results, for preliminary airframe design structural optimization - Perdikoulis, P. V.; Theotokoglou, Efstathios E.; Giannopoulos, Ioannis K. (International Centre for Numerical Methods in Engineering (CIMNE), 2021)
External airframe structural components facing the aircraft flight direction, are prone to bird collisions. Aircraft manufacturers meet the bird strike airworthiness requirements through physical bird strike testing. Mainly due to the high costs involved in the certification process, recent studies have highlighted the capabilities and benefits of hybrid simulation-experiment techniques that reduce certification costs. The numerical investigation presented herein, studied the bird-strike simulation methodologies implemented to support airframe manufacturers to partially fulfill the current certification airworthiness requirements. The methodology can be also applied during preliminary aircraft parametric design stages. In the current study, the method was applied onto an aircraft wing leading edge preliminary design, which led to design exploration by correlating the leading edge skin materials and thicknesses with the rib pitch positioning. The bird-strike impact model was simulated using the Smoothed Particle Hydrodynamics numerical method using ABAQUS® Explicit finite element package. The materials benchmarked were aluminum alloy 2024-T3, carbon fiber reinforced epoxy IM7/8552 and S2 glass Fiber Metal Laminate GLARE®. The design goal of the case study was to provide with preliminary evidence for impact resistance, quantified as residual permanent structural deformation of the critical structural components for which design charts were drawn and presented herein
Keywords: Smoothed Particle Hydrodynamics; Explicit Finite Element Analysis; Aircraft Design; Fiber Metal Laminate; Bird Strike